2016
DOI: 10.7717/peerj.2083
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming decreases arbuscular mycorrhizal fungal colonization in prairie plants along a Mediterranean climate gradient

Abstract: Background: Arbuscular mycorrhizal fungi (AMF) provide numerous services to their plant symbionts. Understanding climate change effects on AMF, and the resulting plant responses, is crucial for predicting ecosystem responses at regional and global scales. We investigated how the effects of climate change on AMF-plant symbioses are mediated by soil water availability, soil nutrient availability, and vegetation dynamics.Methods: We used a combination of a greenhouse experiment and a manipulative climate change e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…Site, treated as a random effect, was not significant in any model that took into account the differential N:P and soil moisture between sites, so it was excluded from analyses in favor of these variables. More extensive site characterization supports this approach to analysis ( Wilson, 2012 ; Pfeifer-Meister et al, 2013 ).…”
Section: Methodsmentioning
confidence: 65%
“…Site, treated as a random effect, was not significant in any model that took into account the differential N:P and soil moisture between sites, so it was excluded from analyses in favor of these variables. More extensive site characterization supports this approach to analysis ( Wilson, 2012 ; Pfeifer-Meister et al, 2013 ).…”
Section: Methodsmentioning
confidence: 65%
“…As shown by Augé et al (2015) mycorrhiza promotes an increase of about 10% when air temperature is less than 27 °C but negative increases at higher temperatures. In another study, it is reported that an increase in air temperatures of 3 °C reduces colonization by mycorrhiza (Wilson et al 2016). The decline in the activity of mycorrhiza at high temperatures is also reported by Mohan et al (2014).…”
Section: Numbers Of Leavesmentioning
confidence: 62%
“…For example, climate change is likely to impact the dispersal of mycorrhizal fungi, key symbionts of trees, which may in turn limit tree migration and colonisation of novel habitats (Pickles et al 2015). Warming may induce a decrease in arbuscular mycorrhizal fungal colonisation, as has been demonstrated in a manipulated Mediterranean climate, with a likelihood of significant impacts on plant communities and ecosystem function (Wilson et al 2016).…”
Section: Challenges In Biocontrol Of Tree Pathogens and Pests With Enmentioning
confidence: 99%